The Effect of Earning per Share and Market Value Added on Stock Return in Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2017-2019 - Fika Aryani; Niken Putri Syawalliawaty (Neraca : Jurnal Akuntansi Terapan, 2021)
This research aims to axamine the effect of Earning per share and Market Value Added variables om stock Return. This research is categorized as associative research. And  uses a quantitative approach by taking data in the form of financial reports obtained from the Indonesia Stock Exchange. Samples taken using purposive sampling method are 19 companies with 48 samples. The analysis used is descriptive statistics, statistical tests and multiple linear regression analysis to see the coefficient of determination, the F statistical value and the statistical value used in hypothesis testing. The results of this research indicate that partially earning per share has a positive and significant effect on stock return, with a significance level of  0.05. And Market value Added give no effect to the stock return.  Whereas the Earning Per Share and Market Value Added simultaneously significant effect   significant effect on stock returns